CRHBP polymorphisms predict chronic pain development following motor vehicle collision. Issue 1 (January 2016) - Linnstaedt, Sarah D.; Bortsov, Andrey V.; Soward, April C.; Swor, Robert; Peak, David A.; Jones, Jeffrey; Rathlev, Niels; Lee, David C.; Domeier, Robert; Hendry, Phyllis L.; McLean, Samuel A.
Abstract : Abstract: Musculoskeletal pain (MSP) is a common sequela of traumatic stress exposure. While biological factors contributing to chronic MSP after motor vehicle collision (MVC) have traditionally focused on tissue injury, increasing evidence suggests that neuro/stress/immune processes mediated by stress system activation may play a more dominant role. In a previous study, we found that genetic variants in the hypothalamic–pituitary–adrenal (HPA) axis–related gene FKBP5 influence vulnerability to persistent MSP 6 weeks after MVC. In the present cohort study (n = 855), we evaluated whether genetic variants in several other important HPA axis–related genes, including the glucocorticoid receptor ( NR3C1 ), corticotropin-releasing hormone receptor R1 ( CRHR1 ), and corticotropin-releasing hormone-binding protein ( CRHBP ), influence risk of chronic MSP over time after MVC. Genetic polymorphism rs7718461 in the CRHBP gene showed significant association ( P = 0.0012) with overall pain severity during the year after MVC in regression models controlling for multiple comparisons. Two additional CRHBP alleles in high linkage disequilibrium with rs7718461 also showed trend-level significance. In secondary analyses, a significant interaction between this CRHBP locus (minor allele frequency = 0.33) and time was observed ( P = 0.015), with increasing effect observed over time following trauma. A significant CRHBP × FKBP5 interaction was also observed, with substantially increased MSP after MVC in those with a risk allele in both genes compared with either gene alone. The results of this study indicate that genetic variants in 2 different HPA axis genes predict chronic MSP severity following MVC and support the hypothesis that the HPA axis is involved in chronic post-MVC MSP pathogenesis. Abstract : The results of this paper support the hypothesis that the hypothalamic–pituitary–adrenal axis is involved in chronic pain pathogenesis following motor vehicle collision trauma.Supplemental Digital Content is Available in the Text.